FORMULASI DAN UJI AKTIVITAS GEL LENDIR BELUT (Monopterus albus) SEBAGAI PENYEMBUH LUKA BAKAR - Fathnur Sani K.; Agung Giri Samudra; Enda Oktri Mayora (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Eel mucus (Monopterus albus) contains bioactives such as glycoprotein, lectin, hemagglutinin and hemolysin. This bioactives are ejected through the mucus glands of the eel skin (Monopterus albums) and has an antibacterial effectivity. The aim of this study is to know the potential of eel mucus gel to treat burn wounds on rabbit. The method used on this study is laboratoric experimental method, thus randomized controlled design using 4 male rabbits divided into 4 groups equally that each group contain 1 male rabbit. The treatment of gel given differently to each group, which are F0, F1, F2 F3 also as positive control used Bioplacenton 0,1 gram. The data obtain are diameters of burn wounds. Data was analyze statistically using one way anova and then followed by LSD and Duncan test. The result of anova test showed there was a significant difference between the treatment group and control negative (p<0,005). The result also showed that F3 are the best dosage with the wound healing percentage 94,79% then followed by F2 and F1.